Clinical Value of Plasma Soluble Urokinase-Type Plasminogen Activator Receptor Levels in Term Neonates with Infection or Sepsis: A Prospective Study. (5th May 2014) - Siahanidou, Tania; Margeli, Alexandra; Tsirogianni, Chrysanthi; Charoni, Stavroula; Giannaki, Maria; Vavourakis, Eustathios; Charisiadou, Athina; Papassotiriou, Ioannis
Abstract : Background . suPAR, the soluble form of the urokinase-type plasminogen activator receptor, has been identified as a biomarker of infection in adults but its properties in neonatal infection are not known. Methods . Plasma suPAR levels were determined by ELISA in 47 term neonates with infection (19 bacterial and 28 viral) and in 18 healthy neonates as controls. Thirteen out of 47 infected neonates were septic. In all infected neonates, suPAR levels were repeated at 24 hours, 48 hours, 3–5 days, and 7–10 days following admission. Results . Plasma suPAR levels were significantly increased in infected neonates upon admission, whereas they were highest in septic neonates, in comparison with controls P < 0.001 and correlated positively with serum CRP levels (P = 0.001 ). At infection subsidence, suPAR concentrations decreased significantly in comparison with baseline (P < 0.001 ) but remained higher than in controls (P = 0.01 ). Receiver operating characteristic analysis resulted in significant areas under the curve for detecting either infected or septic neonates, but not for discriminating between bacterial and viral cause of infection. Conclusions . suPAR is a diagnostic biomarker of infection or sepsis in term neonates; however, it cannot discriminate bacterial from viral infections and also its utility for monitoring the response to treatment is questioned.